Application Value of Segond Fracture Imaging Features in Lateral Knee Instability - Weihong HE; Xi FU; Tingsong FANG; Guining WANG; Juan WANG (CT Lilun yu yingyong yanjiu, 2023)
Objective: To evaluate the imaging features of the Segond fracture and explore its clinical value in lateral instability of the knee joint. Methods: We retrospectively analyzed 45 cases of the Segond fracture. This involved the analysis of the characteristics of the fracture, including the relationship between the fracture and the ligaments around the knee joint, meniscus injury, and the size and location of the fracture block. Moreover, the significance of the Segond fracture in clinical treatment was discussed. Results: Among 45 cases of the Segond fracture, 41 (91.11%) had anterior cruciate ligament (ACL) injury, 31 (68.89%) had anterolateral ligament (ALL) injury, and 12 (26.67%) had iliotibial bundle (ITB) injury. The ALL were all attached to the fracture block, and 25 cases (55.55%) were attached to the ITB. The larger the size of the fracture block and the smaller the distance from the center of Gerdy's nodule, the more likely that the fracture block was attached to the ITB. Conclusion: The Segond fracture is often associated with ACL injury, involving the ALL and ITB. The larger the fracture block and the closer to the center of Gerdy's nodule, the greater the possibility of ITB involvement. Therefore, patients with Segond fractures should be alert to lateral instability of the knee joint.